Peran Kepemilikan Manajerial dalam Memoderasi Hubungan Profitabilitas, Likuiditas dan Struktur Modal dengan Kualitas Laba - Suriani br. Ginting; Anita Tarihoran; Robinhot Gultom (Universitas Methodist Indonesia, 2025)
This study aims to determine and analyze the role of managerial ownership in moderating the relationship between Profitability, Liquidity, and Capital Structure with Earnings Quality. The research subjects were manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The sampling technique used was purposive sampling, with 62 companies meeting the criteria, resulting in 248 observations. The analysis method used was a two-stage approach using the SmartPLS application. The results showed that Profitability, Liquidity, and Capital Structure did not significantly influence earnings quality. The results of the moderation test indicated that managerial ownership was unable to moderate the relationship between Profitability, Liquidity, and Capital Structure with earnings quality.